Paediatric hospital visiting policies in Cameroon : the experiences of nurses and parents : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Arts in Nursing at Massey University, Palmerston North, New Zealand - Njeba, Patience Yenseh (Massey University, 2001)
This study explored the experiences of parents and nurses caring for hospitalised children with the parents either living-in or having only visiting rights. The participants were parents with children hospitalised for a minimum of three days and nurses working in the paediatric ward for a minimum of six months. A qualitative approach using semi-structured interviews and participant observation was used to collect the data and Burnard's (1991) thematic content analysis to analyse the data. Six themes were identified of which two (one from the nurses and one from the parents) are main themes. The main theme from the nurses relates the nurses' aim of meeting the children's need and getting them ready for discharge home. The main theme from the parents relates the parents' satisfaction with the care they receive and the difficulties they have as parents not always being able to be with their child at will. The roles of parents and the nurses with regards the cares of children are relatively distinct in the hospital. The parents' role seemed quite limited due to the poor information received from the nurses although they (nurses) had a better understanding of what these roles could be. It could be noted that attitudes and opinions of nurses and parents about the way children are cared for in hospitals are different. For some parents, living-in and carrying out basic cares such as bathing, changing, feeding and comforting the child is just normal. Others felt it is the nurses' responsibilities, hence were reluctant to do it. Nurses also had divided views with regards to providing this basic care for the children added to their nursing/medical cares. As well there were few nurses to provide the care. Despite the differences, the nurses and parents have a common goal of getting the child ready for discharge home. On the whole the nurses are happy to have parents live-in and parents are happy to stay, although some parents feel living-in is an obligation not a choice. Unlike the parents of the older children that are happy to live-in, the neonatal parents are not given that privilege to live-in and that is distressing to them. The different concepts of care in paediatric wards are examined and not all of the concepts can be applicable in the Cameroon context. The study suggests a possible concept of care to be used in the hospital after a review by the authorities. This study provides a base for future research in this domain.
Keywords: Cameroon; Children -- Hospital care; Nurse and patient; Parent and child